THE INFLUENCE OF ONLINE NEWS CREDIBILITY, SOCIAL MEDIA CONTENT, AND PRINT MEDIA VARIETY ON CUSTOMER TRUST LEVELS - Agustan Agustan; Amiruddin K; Abdul Wahid Haddade; Andi Muhammad Ali Amiruddin; Agus Miranto (FINANSIA : Jurnal Akuntansi dan Perbankan Syariah, 2025)
Consumer trust in Islamic banks is currently declining. Islamic banks are perceived to be the same as conventional banks due to various cases about Islamic banks reported by the mass media. The aim of this research is to analyze the influence of the credibility of online news, the quality of social media content, and the variety of print media on the level of trust of BSI customers. This study uses an associative quantitative approach with simple random sampling techniques. A total of 121 respondents were selected from a total population of 480 using Slovin's formula and analyzed with SEM-PLS. The research results show that the credibility of online news, the quality of social media content, and the variety of print media have a positive and significant impact on customer trust levels. The negative stigma of society is growing stronger due to online news that is reinforced by social media and print media. Practical implications include more effective marketing and communication strategies to maintain customer trust amidst the challenges of the digital era.